A Performative Reading of a Postcard Never Sent. Simondon, Derrida and Performance - Arrarás, Agustina (2024)
This article uses some of the illustrations offered by Simondon in his never-sent letter to Derrida to analyse the programme of techno-aesthetics. This analysis includes not only what is meant by techno-aesthetic sensibility, but also the delayed trajectory of this correspondence in the light of Derrida´s theory of performativity, of which the postal device emerges as a privileged figure. Finally, the two approaches are intertwined in order to reflect on possible contributions and problematisations of performance studies today.